IMMUNOHISTOCHEMICAL EVIDENCE FOR XANTHINE OXIDOREDUCTASE IN HUMAN MYOCARDIUM (Sciences & Technology. A, exactes sciences, 2002)
Xanthine oxidoreductase (XOR) could be an important source of reactive oxygen species (ROS) in the heart. The enzyme is clearly active in rat heart but its present in the human heart is controversial. This study was to detect XOR immunohistochemically in human myocardium using mouse raised monoclonal antibodies to purified human and bovine milk XOR. We assayed the presence of the enzyme in explanted human heart and compared to rat heart results. Using positive and negative controls, immunoactive XOR in heart was clearly present in the cardiomyocytes and in the smooth muscle cells of blood vessels in both species. The endothelial cells showed no staining in the smaller blood vessels. Other data suggest that ROS generating desulpho-type of XOR,  present in rat heart,  inactive with the substrate (hypo)xanthine is active using  NADH as substrate, producing ROS. We speculate that this type of XOR plays a role in radical-induced cardiovascular disease.